PASCAKEBENARAN (POST-TRUTH) DALAM KEHIDUPAN SOSIAL - Pebrianto, Marhan; Mulyono, Yatin (CV. Lafadz Jaya, 2024)
This research aims to analyze post-truth phenomena and their impact in the context of social life. Post-truth, which is an era where lies can be disguised as truth, has changed the information landscape and public perception. This article explores the concept of post-truth from a philosophical and contextual perspective. Additionally, its impact on social polarization and public opinion is also explored. The polarization of society is increasing because post-truth strengthens divisions between groups with different views. This influences public opinion, where emotions and personal beliefs often take precedence over facts. This article also discusses educational and public policy strategies that can be used to address the negative impacts of post-truth. Increasing media literacy, information transparency, moral education, and cooperation between government, media, and educational institutions are the keys to facing this challenge. Thus, this article provides an in-depth understanding of the post-truth phenomenon and attempts to overcome its impact in social life.